Identifikasi Pola Aliran Dua Fasa Uap-Kondensat Berdasarkan Pengukuran Beda Tekanan pada Pipa Horisontal - Sukamta Sukamta; Indarto Indarto; Purnomo Purnomo; Tri Agung Rohmat (Semesta Teknika, 2010)
An experiment of two-phase flow patterns of steam-condensate based on differential pressure measurement in horizontal tube was conducted by varying the flow rate of the steam. The experiment utilised annulus pipe with inner section test pipe was made from copper and outer section was made from Galvanized Iron Pipe (GIP) wrapped with a 10-mm-thick insulation. The pipe was 1.6 meter length, and 4 inch outer diameter and 17 mm inner diameter. The two-phase flow regime was investigated based on pressure gradien between its inlet and outlet. In order to support the result, visualition was conducted using a ¾ inch diameter and 1.3 m length of transparent pipe connected with the test pipe section. Five variations of steam flow rate ranging from 0.00211361 m3/s to 0.007078511 m3/s were selected. The results show that for lowest steam flow rate, stratified flow pattern was identified while for the ot her variations, stratified, wavy, plug and slug flow pattern were observed. Wavy flow pattern occured on transition of stratified to slug or plug. Annular flow pattern was not observed in this experiment. Generally speaking, an increase in steam flow rate resulted in a more significant pressure gradient signals.